Personal carbon footprint app - Shanbhag, Dhruv Narayan (Nanyang Technological University, 2022)
In today’s world, the effects and impact of climate change are very evident. Over several generations, our usage of natural resources, both for personal and professional needs has skyrocketed. This has impacted the ecosystem on several levels, for which the most evident effect is the steady rise in CO2, global temperatures and, by extension, the rise in water levels. Thus, this project aims to create a mobile application that can help users track their carbon footprint on an individual level. It will provide users with recommendations for improvement and will make them aware of the very real effects of global warming. This application will be built using Flutter and Firebase in combination with specific APIs and other libraries.